Seismic fragility analysis of concrete encased frame‐reinforced concrete core tube hybrid structure based on quasi‐static cyclic test. (16th August 2019) - Xiao, Yunfeng; Zeng, Lei; Chen, Yiguang; Du, Guofeng; Zhang, Jicheng; Chen, Juan
Summary: Concrete‐encased frame‐core tube hybrid structural system has been widely employed in high‐rise buildings. This paper intends to analyze the seismic fragility of this structural system under ground motion excitation. The quasistatic cyclic test on a 1/5‐scaled, 10‐story three‐bay specimen is introduced. Fiber‐based finite element model is developed and integrated with numerical techniques that would be able to simulate the nonlinear response based on the OpenSees program. As the model is verified by the experimental data, a series of incremental dynamic analyses (IDAs) considering different frame‐tube stiffness ratios are carried out. IDA curves are drawn to describe each structural performance state. Fragility curves and probabilistic demand models are proposed for quantifying failure probability. The collapse margin ratio is employed to evaluate the collapse probability. The result shows that the collapse probability under rare earthquake still meets the requirement of Applied Technology Committee‐63 Report. The hybrid structure is proved to perform superior collapse resistance ability. The proper increase in the stiffness of core tube can reduce the collapse probability and enhance the collapse resistance capacity.